1991
DOI: 10.1159/000172025
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Study on the Necessity for Routine Nasogastric Intubation after Major Abdominal Surgery

Abstract: The necessity for routine postoperative nasogastric intubation was studied in a group of 149 patients. All patients underwent major abdominal surgery. The patients were randomized preoperatively in a group without a nasogastric tube (group A, n = 74), or in a group with a nasogastric tube for at least 36 h postoperatively (group B, n = 75). No differences between the groups were found in postoperative physical signs as first bowel sounds, passage of first flatus, first defecation, and resumption of normal oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In 4 trials, 1,4,29,32 earlier return of flatus passage in favor of no NGI was reported, with a mean of a half day. In 1 of these trials, 1 this difference was not significant (0.30 days; 95% CI, −0.02 to 0.62 days).…”
Section: Gi Functionsmentioning
confidence: 98%
See 4 more Smart Citations
“…In 4 trials, 1,4,29,32 earlier return of flatus passage in favor of no NGI was reported, with a mean of a half day. In 1 of these trials, 1 this difference was not significant (0.30 days; 95% CI, −0.02 to 0.62 days).…”
Section: Gi Functionsmentioning
confidence: 98%
“…Allocation was by means of randomization (ie, sealed envelopes) in 1 trial, 4 by day and month in 1 trial, 20 and by tables of random numbers in 2 trials 3,21 ; the method of randomization was not stated in 10 trials. 1,19,[22][23][24][25][26][27][28][29] Randomization was based on a computerized randomization table only in 3 trials. [30][31][32] Therefore, concealment of allocation was ensured only in these 3 trials.…”
Section: Trial Qualitymentioning
confidence: 99%
See 3 more Smart Citations